The Microbiome, an Important Factor That Is Easily Overlooked in Male Infertility - Wang, Hefeng; Xu, Anran; Gong, Liping; Chen, Zhaowen; Zhang, Bin; Li, Xiuyun (Frontiers in Microbiology, 2022)
Humankind has been interested in reproduction for millennia. Infertility, in which male factors contribute to approximately 50%, is estimated to concern over 72 million people worldwide. Despite advances in the diagnosis, medical treatment, and psychosocial management of male infertility over the past few decades, approximately 30% of male infertility is still thought to be idiopathic. Despite emerging advances in the microbiome associated with male infertility have indicated that the microbiome may be a key factor to the management of male infertility, the roles and mechanisms of the microbiome remain ambiguous. Here, we mainly discussed the association between microbial infection in the genital tract and male infertility, the effect of antimicrobial therapy on male reproduction, the association between microbial dysbiosis and male infertility, and the effect of probiotic intervention on male reproduction. This review made progress towards establishing a relationship between the microbiome and male infertility, and explored the role of the microbiome in male infertility. We call for more high-quality studies to focus on the relationship between microbes and male infertility, and strongly suggest increasing awareness among sterile males with microbial infection and/or microbial dysbiosis when they seek fertility help.